2010
DOI: 10.1089/fpd.2009.0382
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the First Extended-Spectrum β-Lactamase–Producing NontyphoidalSalmonellaStrains Isolated in Tehran, Iran

Abstract: The infections caused by Salmonella remain a significant public health problem throughout the world. beta-Lactams and fluoroquinolones are generally used to treat invasive Salmonella infections, but emergence and spread of antibiotic-resistant strains are being increasingly notified in many countries. In particular, detection of extended-spectrum beta-lactamases (ESBLs) in Salmonella spp. is a newly emerging threat worldwide. This study was carried out to characterize beta-lactamase-producing Salmonella strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
(36 reference statements)
0
22
1
Order By: Relevance
“…The emergence and spread of antibiotic resistant strains particularly the detection of the Extended Spectrum Beta-lactamases (ESBLs) Salmonella species, is fast becoming an emerging world threat [1]. ESBLs frequently occur in K. pneumoniae but recent studies have increasingly reported its occurrence in the Salmonella specie and other gram-negative organisms [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence and spread of antibiotic resistant strains particularly the detection of the Extended Spectrum Beta-lactamases (ESBLs) Salmonella species, is fast becoming an emerging world threat [1]. ESBLs frequently occur in K. pneumoniae but recent studies have increasingly reported its occurrence in the Salmonella specie and other gram-negative organisms [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…cefuroxime, third generation cephalosporin and aztreonam) with cephamycins and carbapenems as exceptions. Most ESBLs belong to the Ambler class "A" β-lactamases and are inhibited by β-lactamase inhibitors (clavulanate, sulbactam and tazobactam) [1]. ESBLs are plasmid-mediated and as a result, are easily transmitted among members of the Enterobacteriaceae family [2].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the genus Salmonella infect a wide variety of hosts and cause diseases in many animal species and in human beings according to their antigenic profiles [2,3]. Salmonellosis is associated with medium to severe morbidity and even mortality in farm animals, representing major economic losses in the food and animal industries [4].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing occurrence of antimicrobial resistant Salmonella strains have complicated the treatment process. In particular, detection of fluoroquinolon and expanded spectrum cephalosporin's resistant Salmonella strains is a newly emerging threat in many countries (3). In this study, we report a ciprofloxacin and expanded spectrum cephalosporin's resistant Salmonella Enteritidis isolated from a child with severe gastroenteritis.…”
Section: Introductionmentioning
confidence: 82%
“…The isolate was investigated for ESBL production using the double disk synergy test according to published methods (3). The genes responsible for the ESBL phenotype (blaTEM, blaSHV, blaCTX-M) were identified by PCR assay using primers and conditions reported previously (3). By PCR assays the Salmonella Enteritidis isolate was found to carry class 1 integrons (Figure 1).…”
Section: Case Reportmentioning
confidence: 94%